Gold Monetization and Gold Discipline - Flood, Robert P.; Garber, Peter M. (Journal of Political Economy, 1984)
The substantial U.S. inflations of the 1970s led to some popular support for commodity-based money. Gold has had a special role in historical commodity-money schemes, and it emerged as a leading contender in recent discussions. In October 1980 Congress established the Gold Commission to study the possible remonetization of gold. In this paper we analyze some gold monetization schemes proposed to the commission. We find that the adoption of these proposals need not lead to the price-level stability their proponents seek. Even a well-designed commodity-money scheme is a foolproof inflation guard only when the scheme's permanence is guaranteed. Permanence may possibly be guaranteed by an underlying political economy that abhors inflation, but merely the enactment of a new ephemeral rule does not ensure permanence.